MANTRA RITUAL BULEAN MASYARAKAT TALANG MAMAK: KAJIAN SEMIOTIK - Silitonga, Astri Ferani; Elmustian, Elmustian; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to find out the icons, indexes, and symbols found in the mantra ritual bulean in Talang Mamak community. The type of research applied is qualitative with descriptive method of semiotic approach. Technique of collecting data in this research is labeling documentation technique. The data collected is obtained from the medical treatment book of Talang Mamak community in Indragiri Hulu Regency. The data have been analyzed using Charles Morris theory with several stage: data presentation, data discussion, data analysis and conclusion drawing. Viewed from the semiotic side, the writer get the icon, index, and symbol in spell of ritual bulean in society Talang Mamak found one hundred fifty five data. Icon data found as many as fifty two data. Index data found as many as thirty-one data. The symbol was found for seventy-two data.Keywords: Bulean rituals, spells, semiotics.